Surviving Situational Suffering - Barry Chametzky (Grounded Theory Review: An International Journal)
Administrators at post-secondary institutions in the United States hire contingent faculty members to teach a great many classes. It is therefore valuable to understand what the issues are for these on-demand, non-tenured faculty members. The theory of surviving situational suffering explains how part-time adjunct educators in the United States resolve their main concern—maintaining employment—within a context of reduced appreciation, underutilization, and ingratitude. Just as with various historical events now considered discriminatory, the theory explores a form of bias and intolerance in higher education that needs to be openly discussed and addressed. The theory consists of three broad categories: (a) limiting, (b) balancing conflict, and (c) falling short. Though the substantive area is post-secondary educational institutions, the ideas presented in this paper are easily generalizable to other areas in life whenever someone is trying to survive situational anxieties.